Maintained deep brain stimulation for severe dystonia despite infection by using externalized electrodes and an extracorporeal pulse generator. - Hyam, J; de Pennington, N; Joint, C; Green, A; Owen, S; Pereira, E; Aziz, T (2010)
Infection in the context of implant surgery is a dreaded complication, usually necessitating the removal of all affected hardware. Severe dystonia is a debilitating condition that can present as an emergency and can occasionally be life threatening. The authors present 2 cases of severe dystonia in which deep brain stimulation was maintained despite the presence of infection, using ongoing stimulation by externalization of electrode wires and an extracorporeal pulse generator. This allowed the infection to clear and wounds to heal while maintaining stimulation. This strategy is similar to that used in the management of infected cardiac pacemakers. The authors suggest that this prolonged extracorporeal stimulation should be considered by neurosurgeons in the face of this difficult clinical situation.